Association of Caribbean States : integrating the Caribbean (Association of Caribbean States Port of SpainTT, 1999)
Deals with such topics as accelerating the pace of integration; the Fourth Ministerial Meeting and the Second ACS Summit; the Panama Canal; future directions of the ACS; trade and development in Central America; globalisation and regional integration; telecommunications; electronic commerce; Caribbean tourism; the banana crisis; natural disasters; an, linguistics integration for the Caribbean.
5th Ministerial Meeting December 1999